2021
DOI: 10.1101/2021.03.29.437532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stepwise maturation of the peptidyl transferase region of human mitoribosomes

Abstract: Mitochondrial ribosomes are specialized for the synthesis of membrane proteins responsible for oxidative phosphorylation. Mammalian mitoribosomes diverged considerably from the ancestral bacterial ribosomes and feature dramatically reduced ribosomal RNAs. Structural basis of the mammalian mitochondrial ribosome assembly is currently not understood. Here we present eight distinct assembly intermediates of the human large mitoribosomal subunit involving 7 assembly factors. We discover that NSUN4-MTERF4 dimer pla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…Analysis of the methylation of 16S mt-rRNA nucleotides in MRM1-3 knock-out models showed that the 2'-O-methylation of U1369 by MRM2 depends on the prior modification of U1370, substrate of MRM3 (Figure 1). This implies that MRM3 exerts its activity over the assembling mtLSU prior to MRM2, adding molecular evidence to support structural findings (Chandrasekaran et al, 2021;Cheng et al, 2021;Hillen et al, 2021;Lenarčič et al, 2021).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Analysis of the methylation of 16S mt-rRNA nucleotides in MRM1-3 knock-out models showed that the 2'-O-methylation of U1369 by MRM2 depends on the prior modification of U1370, substrate of MRM3 (Figure 1). This implies that MRM3 exerts its activity over the assembling mtLSU prior to MRM2, adding molecular evidence to support structural findings (Chandrasekaran et al, 2021;Cheng et al, 2021;Hillen et al, 2021;Lenarčič et al, 2021).…”
Section: Discussionmentioning
confidence: 55%
“…The late stages of mtLSU assembly involve almost exclusively the remodelling of interfacial RNA elements of otherwise complete particles, as shown by recent structural studies (Chandrasekaran et al, 2021;Cheng et al, 2021;Hillen et al, 2021;Lenarčič et al, 2021). Key players include the helicase DDX28, which dislocates the central protuberance to increase solvent exposure of the intersubunit interface, the MTERF4:NSUN4 complex, which holds H68-71 of domain IV of 16S mt-rRNA in an immature conformation to allow access of assembly factors to the PTC, and the GTPases GTPBP5, GTPBP6, GTPBP7 and GTPBP10, which coordinate the maturation of the PTC through a series of conformational rearrangements.…”
Section: Discussionmentioning
confidence: 93%
“…After methylation of U3039, MRM2 dissociates, whereas GTPBP5 and MTERF4-NSUN4 remain bound (state F). NSUN4 and GTPBP5 cooperate to facilitate folding of the PTC [8,10]. The N-terminus of NSUN4, which is not conserved in its bacterial homolog RsmB, is stabilized by GTPBP5 and protrudes into the PTC.…”
Section: Open Accessmentioning
confidence: 99%
“…On the basis of biochemical data, the next intermediate should contain all ribosomal proteins except bL36m as well as GTPBP10, GTPBP7, and MTERF4-NSUN4 (state B) [7]. MTERF4 and NSUN4 act as another antiassociation module, as they interact with h68-h71 and prevent the folding of structural elements involved in intersubunit bridging [1,[8][9][10][11]. GTPBP7, the homolog of bacterial RbgA, binds early, but it is not clear when GTPBP7 joins the assembling human mtLSU.…”
mentioning
confidence: 99%
See 1 more Smart Citation